Extra-anatomical by-pass - Cuacci, Oscar; Grinfeld, David; Lanari, Néstor (Cirugía del Uruguay, 1978)
The authars clearly state the praceedings and the asis af the extra-anatamical by-pass in the treatment of abstructive arteriopathies in the lower limbs. They present their experience in 20 revascularizatian operations performed in extra-anatamical ways; 9 were axillafemaral by-pass and 12 femorofemoral by-pass,